Question
upstudy study bank question image url

Suppose \( H(x)=5 \sqrt{x}-3 \), Find two functions \( f \) and \( g \) such that \( (f \circ g)(x)=H(x) \). Neither function can be the identity function. (There may be more than one correct answer.) \( f(x)=\square \) \( g(x)=\square \)

Ask by Rowe Powell. in the United States
Mar 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

One possible solution is: \( f(x) = 5x - 3 \) and \( g(x) = \sqrt{x} \).

Solution

We are given \[ H(x)=5\sqrt{x}-3. \] We want to find functions \( f \) and \( g \) such that \[ (f\circ g)(x)=f\bigl(g(x)\bigr)=H(x)=5\sqrt{x}-3. \] One possibility is to let \[ g(x)=\sqrt{x}. \] Then choose \[ f(x)=5x-3. \] Let's verify the composition: \[ (f\circ g)(x)=f(g(x))=5\left(\sqrt{x}\right)-3=5\sqrt{x}-3, \] which matches \( H(x) \). Thus, one valid answer is: \[ \text{\( f(x)=5x-3 \)} \quad \text{and} \quad \text{\( g(x)=\sqrt{x} \)}. \] Both functions are non-identity, satisfying the given requirements. Another possibility (for example) is to choose \[ g(x)=5\sqrt{x} \quad \text{and} \quad f(x)=x-3. \] Here, \[ (f\circ g)(x)=f(5\sqrt{x})=5\sqrt{x}-3, \] which again matches \( H(x) \). Both answers are correct, but one valid answer is: \[ f(x)=5x-3,\qquad g(x)=\sqrt{x}. \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

One way to express \( H(x) = 5 \sqrt{x} - 3 \) as the composition of two functions is to break it down into two simpler parts. Let's choose: \( g(x) = x \) (which is not allowed, but let's start here to simplify our thinking), then, for \( f(x) \), we can define it as: \( f(x) = 5\sqrt{x} - 3 \). However, since both \( f \) and \( g \) must not be identity functions, we revise our \( g \): Let \( g(x) = x^2 \) (this is a valid non-identity function), then: \( f(x) = 5\sqrt{x} - 3 \) becomes \( f(g(x)) = 5\sqrt{x^2} - 3 = 5x - 3 \). To fit better, we can choose: \( g(x) = \frac{x + 3}{5} \), then: \( f(x) = 5\sqrt{x} - 3 \) leads back to H since \( f(g(x)) = 5\sqrt{\frac{x + 3}{5}} - 3 \). Thus, one valid solution could be: \( f(x) = 5 \sqrt{x} - 3 \) and \( g(x) = x^2 \). But let's take a concrete non-identity formulation for both: \( f(x) = 5x - 3 \), \( g(x) = x^{2/5} \). So to summarize, here are the functions: \( f(x) = 5x - 3 \) \( g(x) = x^{2/5} \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy